Analisis Iklim Belajar Siswa Melalui Penerapan Model PjBL pada Pembelajaran Matematika di Kelas II SD - Allya Gustina; Sri Windari; Murjainah Murjainah; Novella Gustikasari (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2026)
This research aims to analyze students' learning climate through the application of the Project Based Learning (PjBL) in mathematics learning in class II of Public Elementary School 002 Palembang. This study used a qualitative descriptive method with the study subjects of grade II students. Data collection techniques are conducted through observation, interviews, and documentation. Data analysis is conducted through the stages of data reduction, data presentation, and conclusions drawn. Research results show that the application of the PjBL model is able to form a more conducive learning climate, characterized by increased focus, attention, and student involvement in the learning process. In addition, interactions between students are becoming more directed, group collaboration is getting better, and activities that interfere with learning can be minimized. Project-based activities involving kinesthetic activities such as shearing and sticking help students become more active, creative, and easier to understand the concept of right triangles more concretely. Student-centered learning also provides an opportunity for them to learn independently and in groups so that the learning experience becomes more meaningful. Thus, the application of the PjBL model can be an effective learning alternative in creating an active, conducive, and enjoyable learning atmosphere for elementary school mathematics and supporting the achievement of learning goals optimally.